1994
DOI: 10.1037/0735-7044.108.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscimol applied to the basolateral amygdala on acquisition and expression of contextual fear conditioning in rats.

Abstract: The amygdala is known to be important for normal aversive Pavlovian learning in the rat. The relative contribution of the amygdala to the learning vs. performance of conditional fear with the GABAa agonist muscimol was assessed. Rats were prepared with cannulas aimed at the basolateral amygdala and trained in a contextual fear conditioning paradigm in which each subject received a series of footshocks in a distinctive observation chamber. Conditional responses evoked after exposure to the observation chamber w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
162
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(183 citation statements)
references
References 23 publications
18
162
3
Order By: Relevance
“…The virtual absence of conditioned fear during tone test in rats conditioned and tested with NMDA in the dorsal hippocampus (experiment 4) is a direct demonstration that the effects of NMDA in the dorsal hippocampus on fear conditioning do not merely reflect state dependency. A similar pattern of results has been obtained with muscimol infusion into the amygdala (Helmstetter and Bellgowan, 1994;Muller et al, 1997). Finally, normal conditioned fear during testing was found in rats that received behaviorally effective infusions of a protein kinase inhibitor or a dopamine antagonist before testing, but not conditioning, into the amygdala (Goosens et al, 2000;Guarraci et al, 2000); of the local anesthetic bupivacaine before conditioning, but not testing, into the nucleus accumbens (Haralambous and Westbrook, 1999); or of a dopamine agonist or antagonist before conditioning, but not testing, into the medial prefrontal cortex (Pezze et al, 2002a;2003).…”
Section: State Dependencysupporting
confidence: 70%
“…The virtual absence of conditioned fear during tone test in rats conditioned and tested with NMDA in the dorsal hippocampus (experiment 4) is a direct demonstration that the effects of NMDA in the dorsal hippocampus on fear conditioning do not merely reflect state dependency. A similar pattern of results has been obtained with muscimol infusion into the amygdala (Helmstetter and Bellgowan, 1994;Muller et al, 1997). Finally, normal conditioned fear during testing was found in rats that received behaviorally effective infusions of a protein kinase inhibitor or a dopamine antagonist before testing, but not conditioning, into the amygdala (Goosens et al, 2000;Guarraci et al, 2000); of the local anesthetic bupivacaine before conditioning, but not testing, into the nucleus accumbens (Haralambous and Westbrook, 1999); or of a dopamine agonist or antagonist before conditioning, but not testing, into the medial prefrontal cortex (Pezze et al, 2002a;2003).…”
Section: State Dependencysupporting
confidence: 70%
“…Moreover, the pharmacological stimulation of GABA A sites or the stimulation of GABAergic neurotransmission in the BLA induced a robust decrease of fear learning (Wilensky et al, 2000). In fact, inactivation of BLA neurons with a GABA A receptor agonist reduces both the acquisition and expression of fear conditioning (Helmstetter and Bellgowan, 1994;Muller et al, 1997;Wilensky et al, 1999). Although abundant evidence has shown that GABA A sites located in projecting pyramidal neurons are critical for an inhibitory control of the BLA excitability (Rainnie et al, 1991b;Sugita et al, 1993;Washburn and Moises, 1992), McDonald and Mascagni (1996) reported an intense GABA A receptor-like immunoreactivity in a subpopulation of nonpyramidal neurons which could play an important dysinhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects are probably not due to drug actions still present on the test days following drug administration. Studies on the involvement of the amygdala in fear conditioning suggest that local microinfusions into single brain areas do not interfere with learning merely on the basis of state dependency (Helmstetter and Bellgowan, 1994;Muller et al, 1997). In any case in this study, the drugs were administered following the liquid consumption to avoid drug influence on the animals' drinking.…”
Section: The Lasting Effect Of Muscimol On Cta Extinctionmentioning
confidence: 99%